2021
DOI: 10.5267/j.msl.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of employee happiness on the relationship between quality of work-life and employee intention to quit: A study on fast-food restaurants in Jordan

Abstract: This study aims to investigate the mediating role of employee happiness in the effect of the quality of work-life on employee intention to quit. Data were collected using a questionnaire developed regarding prior related works. It was administered to a sample consisted of 122 employees selected from four fast-food restaurants in Jordan. Data analysis was conducted using structural equation modelling via Smart-PLS3; the results revealed that the quality of life had significant direct effects on both employee ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The happiness of employees is an integral result for both employees and organisations seeking to maximise their personnel capital's potential (Van De Voorde et al, 2012). The extant literature shows that employee happiness plays a mediating role in several other organisational characteristics/variables (Singh et al, 2018;Alserhan et al, 2021). But to date, studies have yet to be available where the mediating role of employee happiness in the relationship between managerial leadership and turnover intentions is measured.…”
Section: The Mediating Role Of Employee Happinessmentioning
confidence: 99%
See 1 more Smart Citation
“…The happiness of employees is an integral result for both employees and organisations seeking to maximise their personnel capital's potential (Van De Voorde et al, 2012). The extant literature shows that employee happiness plays a mediating role in several other organisational characteristics/variables (Singh et al, 2018;Alserhan et al, 2021). But to date, studies have yet to be available where the mediating role of employee happiness in the relationship between managerial leadership and turnover intentions is measured.…”
Section: The Mediating Role Of Employee Happinessmentioning
confidence: 99%
“…Employees are a vital cornerstone in all organisational efforts because organisations are involved in offering benefits to their end-users via a variety of practices, such as establishing better connections with their clients and enhancing the effectiveness of their services. As a result, businesses must pay close attention to their employees in order to ensure their happiness, commitment, involvement and satisfaction (Alserhan et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high predominance workload, work pressure and long work hours have been a major tendency that increases workaholism among the labour force (Gaudino and Di Stefano, 2023). This has prompted the concern of organisational development practitioners and positive psychologists in search of solutions that will advance the well-being of the workforce and improve organisational performance from time to time (Alserhan et al ., 2021). These extended working hours and work pressure have led to poor productivity and deprivation in the non-work-life domain of employees (Taheri et al ., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also associated with motivation, job participation, job satisfaction, employee health, productivity, job security, competency growth, and work-life balance. (Alserhan et al, 2021;Ghorbani & Khanachah, 2020).…”
Section: Qualitymentioning
confidence: 99%
“…Researchers have found that companies with better employee quality of life have successfully retained their valuable employees and have higher profitability (Anitha, 2014). In a general definition, the quality of work life can be considered the reaction of people to work, especially in satisfaction and mental health, which shape the mental perception of employees' perception of it (Alserhan, Al-Adamat, & Al-Adamat, 2021). Quality of work life has two aspects:…”
Section: Introductionmentioning
confidence: 99%